You fascinate me so the life and times of Cy Coleman - Propst, Andy (Applause Theatre & Cinema Books, 2015)
He penned songs such as Witchcraft and The Best Is Yet to Come (signature tunes for Frank Sinatra and Tony Bennett, respectively) and wrote such musicals as Sweet Charity, I Love My Wife, On the Twentieth Century, and The Will Rogers Follies yet his life has gone entirely unexplored until now. You Fascinate Me So takes readers into the world and work of Tony, Grammy, and Emmy Award winning composer/performer Cy Coleman, exploring his days as a child prodigy in the 1930s, his time as a hot jazz pianist and early television celebrity in the 1950s, and his life as one of Broadways preeminent composers. This first-time biography of Coleman has been written with the full cooperation of his estate, and it is filled with previously unknown details about his body of work. Additionally, interviews with colleagues and friends, including Marilyn and Alan Bergman, Ken Howard, Michele Lee, James Naughton, Bebe Neuwirth, Hal Prince, Chita Rivera, and Tommy Tune, provide insight into Colemans personality and career. Advance Praise for You Fascinate Me So "The great composer Cy Coleman deserves this comprehensive, well-written, and fascinating account of an important career in the musical theater."--Hal Prince, Tony Award-winning producer and director "Cy Coleman is my idol! Although his music was always unmistakably from the fingers and heart of Coleman, Cy could write in any style and always make it both entertaining for the masses yet tasty to we musicians. Reading Andy Propst's book is a wonderful way to relive all the pleasures of Cy Coleman's work." --Marc Shaiman, Tony Award-winning lyricist/composer "Cy did everything his 'own' way. He was unique. Unorthodox. I worked with and was friends with him. I thought I knew pretty much everything about him. Boy, was I wrong. This book is 'one hell of a ride.'" --Michele Lee, actress